The Juridical Analysis of Notary/PPAT Responsibilities who Do Not Pay BPHTB Tax - Eko Kurniawan; Widhi Handoko; Achmad Arifullah (Sultan Agung Notary Law Review, 2022)
One of the potential sources of tax revenue that needs to be explored according to the current economic situation and condition as well as the development of the nation is the type of Customs Tax on Land and Building Rights, hereinafter abbreviated as BPHTB. The transfer of rights to land and buildings can occur due to a legal act or legal event. One of the legal actions that can cause the transfer of rights to land and buildings is through buying and selling. The existence of the transfer of rights must be proven by an authentic deed made by or before the Land Deed Making Official (PPAT). The transfer of rights to land and buildings through the sale and purchase gives rise to tax obligations for the parties, namely Income Tax (PPh) for the seller and Customs for the Acquisition of Land and Building Rights (BPHTB) for the buyer. The purpose of this paper is to describe the legality of the act of receiving the power to deposit taxes by the Land Deed Making Official (PPAT) as a public official and the juridical implications of PPAT who receive the custody of Income Tax (PPh) and Customs for the Acquisition of Land and Building Rights (BPHTB) from taxpayers. The method used to examine these problems is normative legal research using a statute approach to examine the laws and regulations related to the legal issues being studied. The legality of the act of receiving the power to pay taxes by PPAT as a public official actually does not yet exist, in other words, a definite rule has not been established that regulates the act of receiving the power to deposit taxes by PPAT. Then regarding the juridical implications of PPAT who receive PPh and BPHTB tax deposits from taxpayers, even though the act does not have legal legality, its implementation is still included in the legal category because the act departs from the habits that have been in effect so far and is accepted by the community. As long as there is no legal regulation to realize the legality of this act, during that time this habit will continue, although there is no guarantee of legal protection for this act, but as long as it does not cause harm to anyone, it is considered not a problem. The BPHTB fee entrusted by the client to the Notary as the Land Deed Making Officer (PPAT), allows for opportunities for fraud by not paying or embezzling the BPHTB funds deposited. The results show that the deed of sale and purchase that has been made by PPAT is valid even though the taxes arising from the transfer of rights to the land and buildings have not been paid. Parties who do not pay taxes arising from the transfer of land and building rights have debts to the state and may be subject to administrative sanctions in accordance with the provisions of the applicable laws.